Malaria rapid diagnostic test performance : summary results of WHO product testing of malaria RDTs : rounds ... [2008-2009 -]- (WHO GenevaCH, 2010)
Presents summary of the full reports of rounds one to four.
Documentation Centre has: 2008-2009; 2008-2011; 2008-2012